Human adaptation in Antarctic - E. V. Moiseenko (Ukrainian Antarctic Journal, 2006)
People adaptation problem in Antarctic conditions is not insolvable up to now and is the base of medical-biological researches. The purpose of this study was to find out peculiarities in the function of the psychic-physiological and the external respiration and circulation of the human while having a long-term stay under the conditions of Antarctic station.